Model Home Industri Seni : Studi Hasil Pelatihan Pembuatan Busana Tari Dalam Membantu Kemandirian Ekonomi Keluarga - Dewi Karyati; Agus Budiman; Heny Rohayani; Ayo - Sunaryo (Mahesa Research Center, 2020)
The development of the creative home industry in the art sector in Indonesia shows promising growth for those who do it. In its development, many art home industries have grown and developed in the community that have been able to show their independence in supporting the nation's economy. Home Art industries that are currently developing in society include: traditional crafts, traditional musical instrument craftsmen, fashion and dance accessories craftsmen, and so on. The purpose of this study was to determine the model of the art home industry through training programs for making clothes and traditional dance accessories in an effort to empower the potential of housewives as the main actors to help support the family's economic independence. The concept of the art home industry is one of the approaches to the creative industry program in the arts developed by the government. The creative industry is an economic concept in the new era that intensifies information and creativity by relying on ideas and stock of knowledge from human resources (HR) as the main production factors. This training program is carried out in three stages of activity, namely the preparation stage, implementation stage and evaluation stage. Training activity data were obtained from unstructured interviews, observation and activity evaluation questionnaires to measure the accuracy of the training program. The data were analyzed based on a qualitative approach. The results showed that there is a strategic role of dance clothing training activities in an effort to develop the art home industry to empower the potential of housewives in strengthening the resilience of family economic independence.